How artificial intelligence shapes trust and visit decisions on digital tourism platforms in Indonesia - Aris, Valentino; Salam, Nur; Sobirov, Bobur; Rahmatullah, Rahmatullah; Syam, Agus; Bakri, Rizal (Manajemen dan Bisnis, 2026)
This study examines how personalization and interactivity on Indonesia’s digital tourism platforms shape consumer trust and visit decisions. Personalization captures how well a platform tailors content such as destination options, itineraries, and deals to a user preferences, budget, and travel context. Interactivity reflects how responsive and engaging the platform is when users search, compare, ask questions, and adjust plans. Using a cross-sectional survey of 415 users who had used platform features within the past six months. The data were analyzed with PLS-SEM in SmartPLS 4. The results show that both personalization and interactivity positively and significantly increase consumer trust, with personalization emerging as the strongest driver. For visit decisions, personalization and interactivity also have significant positive effects. However, consumer trust does not significantly predict visiting decisions and therefore does not mediate the effects of platform features on visit decision. This suggests a trust–behavior gap where users may feel confident in a platform, yet their final choice is still driven mainly by practical planning value. Tourism platforms should prioritize relevant, context-aware recommendations and responsive planning assistance, while reinforcing decision cues such as clear cost and time estimates and credible social proof to better convert interest into visit decision.